2023
DOI: 10.1371/journal.pone.0267870
|View full text |Cite
|
Sign up to set email alerts
|

Bats as ecosystem engineers in iron ore caves in the Carajás National Forest, Brazilian Amazonia

Abstract: Ecosystem engineers are organisms able to modify their environment by changing the distribution of materials and energy, with effects on biotic and abiotic ecosystem components. Several ecosystem engineers are known, but for most of them the mechanisms behind their influence are poorly known. We detail the role of bats as ecosystem engineers in iron ore caves in the Carajás National Forest, Brazilian Amazonia, an area with > 1,500 caves, some holding ~150,000 bats. We analyzed the chemical composition of gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Where there is a paucity of pollen-based paleoenvironmental reconstruction from lake, wetland, and swamp habitats, bat guano deposits provide an additional archive that fill this data for paleoenvironment reconstruction and paleoecology studies. Over millennial timescale, several meters of guano can accumulate on cave floors [43] , representing an outstanding environmental archive that becomes increasingly attractive for palynologist worldwide [5 , 6 , 10 , 35 , 44] .…”
Section: Methods Validationmentioning
confidence: 99%
“…Where there is a paucity of pollen-based paleoenvironmental reconstruction from lake, wetland, and swamp habitats, bat guano deposits provide an additional archive that fill this data for paleoenvironment reconstruction and paleoecology studies. Over millennial timescale, several meters of guano can accumulate on cave floors [43] , representing an outstanding environmental archive that becomes increasingly attractive for palynologist worldwide [5 , 6 , 10 , 35 , 44] .…”
Section: Methods Validationmentioning
confidence: 99%
“…Their ability to fly long distances and their diverse feeding habits make it easier for them to acquire and spread viruses across remote areas and to transmit them to other species. Additionally, their social structures and behaviors contribute to virus transmission and persistence within bat populations [ 4 , 18 , 19 , 20 ]. However, changes in the environment, such as urbanization, agricultural intensification, and deforestation, have altered the composition and dynamics of bat communities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown an overall decline in species richness and relative abundance associated with urbanization [ 22 ]. Nevertheless, insectivorous bats tend to thrive in large urban environments [ 4 , 18 , 19 ]. Furthermore, the diversity of bat habitats can influence both microbe transmission and persistence in bat communities [ 2 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%